Influence of Cr3+ substitution for Mg2+ on the crystal structure and microwave dielectric properties of CaMg1-xCr2x/3Si2O6 ceramics. Issue 9 (15th June 2019) - Tang, Bin; Xiang, Qiuyuan; Fang, Zixuan; Zhang, Xing; Xiong, Zhe; Li, Hao; Yuan, Changlai; Zhang, Shuren
Abstract: The CaMg1 -x Cr2 x /3 Si2 O6 (0 ≤ x ≤ 0.1) microwave dielectric ceramics were synthesized via conventional solid state reaction. In this study, the effects of Cr 3+ substituting for Mg 2+ on morphology, crystal structure and microwave dielectric properties of CaMg1 -x Cr2 x /3 Si2 O6 ceramics were explored. XRD diffraction patterns exhibited that the CaMg1 -x Cr2 x /3 Si2 O6 ceramics possessed the pure phase of CaMgSi2 O6 when x ≤ 0.06 and a small amount of secondary phase Ca3 Cr2 (SiO4 )3 for 0.08 ≤ x ≤ 0.1. SEM micrographs revealed that the substitution of Mg 2+ with Cr 3+ could decrease the grain size. The apparent density was affected by the concentration of Mg vacancies. The correlation between crystal structure and microwave dielectric properties was investigated through the Rietveld refinement and Raman analysis. The microwave dielectric properties were mainly dependent on relative density, ionic polarizabilities, internal strain Ƞ, disordered structure and MgO6 octahedron distortions. Finally, CaMg1 -x Cr2 x /3 Si2 O6 ( x = 0.02) ceramics sintered at 1270 °C for 3 h exhibited excellent microwave dielectric properties of ε r = 8.06, Q × f = 89054 GHz, τ f = −44.92182 ppm/ºC.